2018
DOI: 10.1001/jamaneurol.2017.3967
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a 3-Dimensional Stent Retriever With Aspiration-Based Thrombectomy vs Aspiration-Based Thrombectomy Alone in Acute Ischemic Stroke Intervention

Abstract: IMPORTANCEThe treatment effects of individual mechanical thrombectomy devices in large-vessel acute ischemic stroke (AIS) remain unclear.OBJECTIVE To determine whether the novel 3-dimensional (3-D) stent retriever used in conjunction with an aspiration-based mechanical thrombectomy device (Penumbra System; Penumbra) is noninferior to aspiration-based thrombectomy alone in AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 26 publications
6
77
3
2
Order By: Relevance
“…At least four trials have explicitly incorporated a reperfusion outcome MCID into study design, power calculations, and interpretation. All were noninferiority trials and used MCID values of 8–15%, all substantially higher than the expert-determined 3.1–5% value identified in the current study ( 10 , 11 , 19 , 20 ). None of the trial reports indicate how its more generous MCID values were derived.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…At least four trials have explicitly incorporated a reperfusion outcome MCID into study design, power calculations, and interpretation. All were noninferiority trials and used MCID values of 8–15%, all substantially higher than the expert-determined 3.1–5% value identified in the current study ( 10 , 11 , 19 , 20 ). None of the trial reports indicate how its more generous MCID values were derived.…”
Section: Discussionmentioning
confidence: 62%
“…A wave of several superiority design trials were first performed and demonstrated the superiority of endovascular thrombectomy over medical therapy alone ( 1 9 ). Thereafter, trials assessing successor variations in thrombectomy device design have generally used noninferiority designs, seeking to demonstrate that newer devices are at least as good as existing devices ( 10 12 ).…”
mentioning
confidence: 99%
“…Initial experience with this approach has shown promising results 6 7. Recent data from the 3D separator trial has provided some support that aspiration is potentially comparable with stent retrievers, as they found no significant difference in revascularization or outcomes between the two groups 8. However, it should be noted that the 3D separator is a novel stent retriever and therefore aspiration was not compared against the established Food and Drug Administration (FDA) approved stent retrievers for stroke treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of aspiration thrombectomy as compared with stent-retriever thrombectomy include the lower theoretical risk of vessel damage including perforation, thrombosis or downstream emboli as traversing the occluding thrombus is not necessary, although systematic review and meta-analyses does not demonstrate any difference in these complications between the two techniques 11. Another potential advantage of aspiration is shorter procedural time, with a reported 7–13 min advantage in groin-to-perfusion time versus stent retrieval in recent studies 11–13. However, there are no significant difference in overall patient outcomes between the two techniques, nor are there any studies reporting significant differences in the rate of occurrence of delayed effects on vessel wall such as stenosis.…”
Section: Discussionmentioning
confidence: 99%